Composite binder aqueous solution, silicon-based negative pole piece, and preparation method and application of silicon-based negative pole piece
By using a composite binder aqueous solution, the mechanical strength and conductivity of the silicon-based negative electrode are enhanced, and the problems of volume expansion and poor conductivity of the silicon-based negative electrode are solved, and the rate performance and cycle stability are significantly improved. It is suitable for commercial applications of lithium-ion batteries.
Patent Information
- Application Number
- CN202411752048.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The silicon-based negative electrode has problems of volume expansion and poor conductivity in lithium-ion batteries, which leads to poor rate performance and cycle stability, hindering its commercialization process.
Using a composite binder aqueous solution, a binder with enhanced mechanical strength and conductive network is prepared by dissolving the aqueous polymer binder with a small molecule physical crosslinker in water, and adding pyrrole and an initiator, which is used to improve the structural stability and electrical conductivity of the silicon-based negative electrode.
It significantly improves the cycling stability and rate performance of the silicon-based negative electrode, can maintain good capacity under high current density, and circulate stably at high surface capacity, meeting the needs of fast charging and high energy density.
Smart Images

Figure CN119570399A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite binder aqueous solution, a silicon-based negative electrode sheet, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have taken a core position in many fields such as electric vehicles, renewable energy storage systems and portable electronic devices due to their high energy density, long cycle life and environmental friendliness. With the increasing global demand for clean energy and the growth of electricity demand driven by technological progress, the development of higher-performance lithium-ion batteries has become particularly important. The next generation of lithium-ion batteries must not only have higher energy density, but also have excellent fast charge and discharge capabilities (i.e. high rate performance) and long service life to meet increasingly complex usage scenarios.
[0003] In this context, silicon has attracted widespread attention as a potential negative electrode material. The theoretical specific capacity of silicon is as high as 3579 mAh g -1 , far exceeding the 372mAh g of the current commercial graphite negative electrode -1 , which makes it possible to achieve a significant increase in battery energy density. However, the application of silicon-based anodes faces major challenges. First, silicon undergoes significant volume changes during the charging and discharging process, up to about 400%. This extreme volume expansion can cause material structure damage, which in turn affects the cycle stability and safety of the battery. Secondly, silicon itself has a low electrical conductivity, which limits its rate performance as a negative electrode material. These factors work together to make it difficult for silicon to perform as expected in actual applications despite its extremely high theoretical capacity, which seriously hinders the commercialization of silicon-based anodes.
[0004] At present, the main strategies to solve the volume expansion problem of silicon-based negative electrodes focus on two aspects: silicon structural design and binder design. In terms of silicon structural design, researchers have proposed a variety of solutions, including porous silicon, silicon nanowires, silicon nanotubes, and hollow core-shell silicon. However, these designs are generally complex in process and costly, making them difficult to commercialize. In contrast, binder design has received widespread attention due to its low cost and obvious effect. As a key component of lithium-ion battery electrode materials, binders are not only responsible for tightly combining active materials, conductive agents, and current collectors, but also determine the overall mechanical properties of the electrode to a certain extent. In response to the volume expansion problem of silicon-based negative electrodes, the current design ideas for binders are mainly concentrated in two directions: one is to enhance the mechanical strength and elasticity of the binder itself so that it can better adapt to the volume change of silicon materials during charging and discharging; the other is to optimize the interaction between the binder and silicon particles, and to inhibit the separation between particles by forming a stronger interfacial bonding force to maintain the integrity of the electrode structure. Although binder design has shown great potential in improving the cycle stability and structural integrity of silicon-based anodes, there are still some technical problems that need to be solved, especially solving the problem of poor rate performance of silicon-based anodes through binder design. So far, there are relatively few reports and patents in related fields, which shows that there is still a lot of research space and challenges in this direction.
[0005] Therefore, it is urgent to develop a new binder to improve the poor rate performance of silicon-based negative electrodes, thereby improving the fast charging and cycle stability of silicon-based negative electrodes under high surface capacity. Summary of the invention
[0006] In view of this, the present invention proposes a composite binder aqueous solution, a silicon-based negative electrode plate and a preparation method and application thereof, and obtains a silicon-based negative electrode composite binder through inexpensive raw materials and a simple preparation process, so as to significantly improve the fast charging and cycle stability of the silicon-based negative electrode under high surface capacity.
[0007] In a first aspect, the present invention provides a method for preparing a composite binder aqueous solution, the method comprising the following steps: dissolving an aqueous polymer binder and a small molecule physical crosslinker in water, adding pyrrole to the mixed solution, stirring, then adding an initiator, and continuing to stir to obtain the composite binder aqueous solution.
[0008] By adopting the above technical solution, the water-based polymer binder and the small molecule physical cross-linking agent are dissolved in water, and pyrrole and initiator are added to significantly enhance the mechanical strength and elasticity of the binder, effectively cope with the volume expansion of the silicon-based negative electrode during the charge and discharge process, and make the silicon-based negative electrode have excellent cycle stability. It can stably cycle more than 500 times in the micron silicon negative electrode, and the micron silicon, silicon / carbon composite and silicon oxide negative electrode are 3mAh cm -2The conductive network formed by pyrrole also improves the electronic conductivity and ion transfer efficiency of the electrode, thereby significantly improving the cycle stability and rate performance of the silicon-based negative electrode, helping the micron silicon half-cell to maintain 1000mAh g at a high current density of 20A / g. -1 The capacity of the micron silicon-NCM811 full battery can be stably cycled 100 times at a fast charge rate of 6C (15 minutes to fully charge). This method is simple and easy to implement, with low cost, and provides a new way for the commercial application of silicon-based negative electrode materials.
[0009] On the basis of the above technical solution, preferably, the mass ratio of the aqueous polymer binder to the small molecule physical cross-linking agent is 1:1 to 3:1.
[0010] On the basis of the above technical solution, preferably, the mass ratio of the pyrrole to the mixed solution is 1:9 to 3:7.
[0011] On the basis of the above technical solution, preferably, the stirring is carried out under ice bath conditions, and the stirring temperature is 0-5°C.
[0012] On the basis of the above technical solution, preferably, the mass ratio of the pyrrole to the initiator is 3:1 to 5:1.
[0013] On the basis of the above technical scheme, preferably, the aqueous polymer binder is selected from one or more of polyacrylic acid, polyvinyl alcohol, carboxymethyl cellulose, sodium alginate, guar gum or konjac glucomannan; the small molecule physical cross-linking agent contains a carboxyl group, and the small molecule physical cross-linking agent containing a carboxyl group is selected from one of citric acid, oxalic acid or succinic acid.
[0014] On the basis of the above technical scheme, preferably, during the polymerization process, the -NH of the pyrrole forms hydrogen bond interactions with -COOH or -OH in the aqueous polymer binder and the small molecule physical cross-linker, so that the water-insoluble polypyrrole forms a uniform composite binder aqueous solution. When preparing the silicon-based negative electrode, the polypyrrole is tightly coated on the surface of the active material through the above hydrogen bond interactions, further improving the rate performance of the silicon-based negative electrode.
[0015] On the basis of the above technical solution, preferably, the initiator is an oxide initiator, and the preferred initiator of the present application is ammonium persulfate.
[0016] On the basis of the above technical solution, preferably, the stirring time is 15 to 60 minutes, and the stirring speed is 200 to 800 r / min.
[0017] In a second aspect, the present invention relates to a composite binder aqueous solution prepared by the above method, wherein the mass fraction of the composite binder aqueous solution is 10 to 40%.
[0018] By adopting the above technical scheme, the preparation conditions of the composite binder aqueous solution are simple, and the good adhesion ability and suitable viscosity range ensure good processing performance and coating uniformity, which is conducive to large-scale production and application.
[0019] On the basis of the above technical solutions, preferably, it involves the application of a composite binder aqueous solution in a silicon-based negative electrode plate.
[0020] In a third aspect, the present invention provides a silicon-based negative electrode plate, comprising the above-mentioned composite binder aqueous solution, a silicon-based material, and a conductive agent.
[0021] On the basis of the above technical solution, preferably, the mass ratio of the composite binder, the silicon-based material and the conductive agent is 1-2:6-8:0-2.
[0022] On the basis of the above technical solution, preferably, the silicon-based material is selected from silicon microparticles, silicon nanoparticles, silicon nanowires, silicon / carbon composites, silicon monoxide or any battery negative electrode material containing silicon.
[0023] On the basis of the above technical solution, preferably, the conductive agent is selected from one of conductive carbon black Super-P, acetylene black and Ketjen black.
[0024] In a fourth aspect, the present invention relates to a method for preparing the above-mentioned silicon-based negative electrode sheet, the method comprising: stirring a composite binder aqueous solution, a silicon-based material and a conductive agent in water for 6 to 72 hours, coating the mixture on a current collector, drying at 40 to 150° C., and pressing to obtain a silicon-based negative electrode sheet.
[0025] On the basis of the above technical solutions, preferably, it involves the application of the above silicon-based negative electrode plate in the field of lithium-ion batteries.
[0026] The composite binder aqueous solution for silicon-based negative electrode plates provided by the present invention has the following beneficial effects compared with the prior art:
[0027] 1. The composite binder for the silicon-based negative electrode plate designed by the present invention optimizes the electronic conductivity and lithium ion transmission performance of the silicon negative electrode, and significantly improves the rate performance of the silicon-based negative electrode.
[0028] 2. The preparation method of the composite binder aqueous solution provided by the present invention increases a large number of hydrogen bonding sites by introducing a small molecule physical cross-linking agent containing a carboxyl group into the aqueous polymer binder, thereby significantly enhancing the mechanical properties of the binder itself. The excellent mechanical properties of the binder further improve the processability of the electrode. At the same time, polypyrrole can be generated by in-situ polymerization in the binder. Through the strong interaction between the binder and the silicon particles, the polypyrrole can be tightly coated on the surface of the silicon particles to form a stable conductive network, which significantly improves the charge transfer capacity of the electrode. In addition, the composite binder also helps to form a solid electrolyte layer rich in Li-N, participates in the formation of a solid electrolyte interface layer, and further enhances its lithium ion transfer capacity. These improvements work together to effectively solve the volume expansion and conductivity problems of silicon-based negative electrodes, significantly improve the rate and cycle stability of silicon negative electrodes at high surface capacity, and the micron silicon negative electrode has a good conductivity of 4A g -1 The current density is 2300mAhg -1 The above good capacity play, at 20A g -1 The high current density can be stabilized at 1000mAh g -1 Cycling. Silicon / carbon and silicon dioxide anodes at 3 mAh cm -2 It can stably cycle more than 100 times under high surface capacity.
[0029] 3. The composite binder aqueous solution prepared by the present invention can be stably circulated in the absence of a conductive agent, and can significantly improve the fast charging performance of the silicon-based negative electrode and the cycle stability at high surface capacity. The full battery matched with the high-nickel positive electrode can stably cycle 100 times at a high rate of 6C (fully charged within 15 minutes), reaching the commercial fast charging standard, and has great market potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 This is a rate performance diagram of the micron silicon half-cell in Example 1;
[0032] Figure 2 The rate performance of the full battery of micron silicon-high nickel ternary positive electrode (NCM811) in Example 2;
[0033] Figure 3 The fast charging performance of the micron silicon-NCM811 full battery in Example 2;
[0034] Figure 4 This is a long cycle performance diagram of the micron silicon half-cell in Example 3;
[0035] Figure 5 This is a long cycle performance diagram of the micron silicon half-cell under high loading in Example 5;
[0036] Figure 6 is a cycle performance diagram of the silicon / carbon half-cell in Example 6;
[0037] Figure 7 Graph showing the cycle performance of the silicon dioxide half-cell in Example 7;
[0038] Figure 8 This is a cycle performance diagram of the micron silicon half-cell in Example 8 without a conductive agent;
[0039] Fig. 9 This is the cycle performance diagram of the micron silicon half-cell at different polypyrrole contents in Comparative Example 3. DETAILED DESCRIPTION
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of the materials mainly involved in the examples are shown in Table 1 below, and the remaining materials not shown are conventional commercial products.
[0042] Table 1 Material source description
[0043] Serial number Material / Equipment Name Specifications / Models factory 1 Polyacrylic acid 100g, average molecular weight 45w Aladdin 2 Polyvinyl alcohol 50g, alcoholysis degree: 87.0~89.0% Aladdin 3 Konjac Glucomannan 25g, purity ≥95% Macklin 4 Citric Acid 500g, purity: 99% Sinopharm 5 Pyrrole 25g, purity 99% Innochem 6 Ammonium Persulfate 500g Sinopharm
[0044] The following are specific embodiments of the present invention.
[0045] Embodiment 1
[0046] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0047] The first step is to prepare a composite binder aqueous solution
[0048] Dissolve polyacrylic acid (2.7 g, water-based polymer binder) and citric acid (0.9 g, small molecule physical cross-linker containing carboxyl groups) in 35.2 ml of water, place in an ice bath at 0-5°C, add pyrrole (0.4 g) to the mixed solution, stir evenly, add 0.8 ml of ammonium persulfate aqueous solution (mass fraction 10%, initiator), stir at 500 r / min for 15 min, and obtain a composite binder aqueous solution.
[0049] Step 2: Prepare silicon-based negative electrode
[0050] Silicon micron particles (0.360 g), the composite binder aqueous solution (1.2 ml) obtained in the first step, a conductive agent (SuperP, 0.120 g) and 1 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, dried at 100°C for 12 hours, and pressed into a sheet to obtain a silicon-based negative electrode sheet.
[0051] Step 3: Prepare lithium-ion batteries
[0052] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0053] Comparative Example 1
[0054] The difference from Example 1 is that pyrrole is not added when preparing the composite binder aqueous solution, and the other steps remain unchanged.
[0055] The performance test of the battery prepared in the above-mentioned Example 1 and Comparative Example 1 includes: performing a constant current charge and discharge test on the button battery assembled in the third step, wherein the current density is 2A / g-20A / g and the voltage window is 0.01-1V. The test results are as follows: Figure 1 shown.
[0056] Depend on Figure 1 It can be seen that when polypyrrole-polyacrylic acid-citric acid is used as a binder and silicon microparticles are used as active materials, the -1 The high current density can be stabilized at 1000mAh g -1 cycle, while the binder without pyrrole is difficult to work normally at the same rate, indicating that the introduction of pyrrole significantly improves the rate performance of the micron silicon negative electrode.
[0057] Embodiment 2
[0058] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0059] The first step is to prepare a composite binder aqueous solution
[0060] Dissolve polyacrylic acid (0.9 g, water-based polymer binder) and citric acid (0.9 g, small molecule physical cross-linker containing carboxyl groups) in 17.6 ml of water, place in an ice bath at 0-5°C, add pyrrole (0.2 g) to the mixed solution, stir evenly, add 0.4 ml of ammonium persulfate aqueous solution (mass fraction 10%, initiator), stir at 400 r / min for 15 min, and obtain a composite binder aqueous solution.
[0061] Step 2: Prepare silicon-based negative electrode
[0062] Silicon micron particles (0.480 g), the composite binder aqueous solution (1.2 ml) obtained in the first step, a conductive agent (SuperP, 0.160 g) and 1 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, dried at 80°C for 12 hours, and pressed into a sheet to obtain a silicon-based negative electrode sheet.
[0063] Step 3: Prepare lithium-ion batteries
[0064] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with NCM811 as the positive electrode and an N / P ratio of 1.15. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and a 10% mass fraction of FEC additive was added.
[0065] Comparative Example 2
[0066] The difference from Example 2 is that pyrrole is not added when preparing the composite binder aqueous solution, and the other steps remain unchanged.
[0067] The performance test of the batteries prepared in the above-mentioned Example 2 and Comparative Example 2 includes: performing a constant current charge and discharge test on the button-type battery assembled in the third step, wherein the voltage window is 3.0-4.2V and the current rate is 0.5C-6C. The test results are as follows: Figure 2 , Figure 3 shown.
[0068] Depend on Figure 2 It can be seen that the full battery with micron silicon anode prepared with polypyrrole-polyacrylic acid-citric acid as binder and NCM811 cathode in this embodiment shows good rate performance at 0.5C-6C. Compared with comparative example 2 without pyrrole, the capacity of polypyrrole-polyacrylic acid-citric acid after 2C rate is significantly different, and the capacity is as high as 145mAh g at 6C. -1 , while the control group was less than 100mAh g -1. This shows that the composite binder can effectively improve the rate performance of micron silicon full cells.
[0069] Depend on Figure 3 It can be seen that the full battery prepared with micron silicon anode and NCM811 cathode using polypyrrole-polyacrylic acid-citric acid as binder in this embodiment is fast charged at 6C (discharged at 0.5C). Compared with the control group without pyrrole, the capacity of polypyrrole-polyacrylic acid-citric acid remains at 129 mAh g after 100 cycles at 6C. -1 Above, while Comparative Example 2 is less than 100 mAh g -1 . This shows that the composite binder can effectively improve the rate performance of micron silicon full cells.
[0070] Embodiment 3
[0071] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0072] The first step is to prepare a composite binder aqueous solution
[0073] Dissolve polyacrylic acid (1.6 g, aqueous polymer binder), konjac glucomannan (0.2 g, aqueous polymer binder) and citric acid (0.2 g, small molecule physical cross-linking agent containing carboxyl groups) in 24 ml of water, place in an ice bath at 0-5°C, add pyrrole (0.6 g) to the mixed solution, stir evenly, add 2 ml of ammonium persulfate aqueous solution (mass fraction 10%, initiator), stir at 800 r / min for 30 min, and obtain a composite binder aqueous solution.
[0074] Step 2: Prepare silicon-based negative electrode
[0075] Silicon micron particles (0.360 g), the composite binder aqueous solution (1.2 ml) obtained in the first step, a conductive agent (SuperP, 0.120 g) and 1 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, vacuum dried at 40°C for 2 hours, dried at 80°C for 6 hours, and pressed into sheets to obtain a silicon-based negative electrode sheet.
[0076] Step 3: Prepare lithium-ion batteries
[0077] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0078] Step 4: Performance Testing
[0079] The button cell assembled in the third step was subjected to constant current charge and discharge tests, where the voltage window was 0.01-1.0V and the current density was 2A / g. The test results are as follows: Figure 4 shown.
[0080] Depend on Figure 4 It can be seen that the battery with polyacrylic acid-konjac glucomannan-polypyrrole-citric acid as the binder and micron silicon particles as the active material shows excellent cycle stability. When the lithium sheet is replaced, the micron silicon negative electrode can stably cycle 500 times, and the remaining capacity remains at 1700mAh g -1 The above indicates that the composite binder can effectively inhibit the volume expansion of the micron silicon negative electrode.
[0081] Embodiment 4
[0082] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0083] The first step is to prepare a composite binder aqueous solution
[0084] Dissolve polyacrylic acid (0.8 g, water-based polymer binder), polyvinyl alcohol (0.8 g, water-based polymer binder) and citric acid (0.4 g, small molecule physical cross-linking agent containing carboxyl groups) in 20 ml of water, heat and stir at 100°C for 8 h, cool and place in an ice bath at 0-5°C, add pyrrole (0.4 g) to the mixed solution, stir evenly, add 4 ml of ammonium persulfate aqueous solution (mass fraction of 10%, initiator), stir at 300 r / min for 60 min, and obtain a composite binder aqueous solution.
[0085] Step 2: Prepare silicon-based negative electrode
[0086] Silicon micron particles (0.480 g), the composite binder aqueous solution (1.6 ml) obtained in the first step, a conductive agent (SuperP, 0.160 g) and 1 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, dried at 80°C for 12 hours, and pressed into a sheet to obtain a silicon-based negative electrode sheet.
[0087] Step 3: Prepare lithium-ion batteries
[0088] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0089] Step 4: Performance Testing
[0090] The button cell assembled in the third step was subjected to constant current charge and discharge tests, where the voltage window was 0.01-1.0V and the current rate was 0.5C-6C.
[0091] Analysis of test results: When polyacrylic acid-polyvinyl alcohol-polypyrrole-citric acid is used as a binder and nano-silicon is used as an active material, the battery exhibits excellent rate performance and cycle stability at high surface capacity.
[0092] Embodiment 5
[0093] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0094] The first step is to prepare a composite binder aqueous solution
[0095] Dissolve polyacrylic acid (0.8 g, water-based polymer binder), polyvinyl alcohol (0.8 g, water-based polymer binder) and citric acid (0.4 g, small molecule physical cross-linking agent containing carboxyl groups) in 20 ml of water, place in an ice bath at 0-5°C, add pyrrole (0.2 g) to the mixed solution, stir evenly, add 2 ml of ammonium persulfate aqueous solution (mass fraction of 10%, initiator), stir at 600 r / min for 60 min, and obtain a composite binder aqueous solution.
[0096] Step 2: Prepare silicon-based negative electrode
[0097] Silicon micron particles (0.360 g), the composite binder aqueous solution (1.6 ml) obtained in the first step, a conductive agent (SuperP, 0.120 g) and 1 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, dried at 80°C for 12 hours, and pressed into a sheet to obtain a silicon-based negative electrode sheet.
[0098] Step 3: Prepare lithium-ion batteries
[0099] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0100] Step 4: Performance Testing
[0101] The button cell assembled in the third step was subjected to constant current charge and discharge test, where the voltage window was 0.01-1.0V and the current rate was 0.3C. The test results are as follows: Figure 5 shown.
[0102] Depend on Figure 5It can be seen that when polyacrylic acid-polyvinyl alcohol-polypyrrole-citric acid is used as a binder and micro-silicon is used as an active material, the battery has a high performance of 3 mAh cm -2 The high surface capacity can be stably cycled for 250 cycles, and the capacity retention rate is greater than 80%, which shows that the composite binder can effectively inhibit the volume expansion of micron silicon.
[0103] Embodiment 6
[0104] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0105] The first step is to prepare a composite binder aqueous solution
[0106] Polyvinyl alcohol (1.4 g, aqueous polymer binder), konjac glucomannan (0.4 g, aqueous polymer binder) and citric acid (0.2 g, small molecule physical cross-linking agent containing carboxyl groups) were dissolved in 20 ml of water, heated and stirred at 80°C for 8 h, and placed in an ice bath at 0-5°C after cooling. Pyrrole (0.2 g) was added to the mixed solution and stirred evenly. 2 ml of ammonium persulfate aqueous solution (mass fraction of 10%, initiator) was added, and stirred at 500 r / min for 60 min to obtain a composite binder aqueous solution.
[0107] Step 2: Prepare silicon-based negative electrode
[0108] The silicon / carbon composite material (0.480 g), the composite binder aqueous solution (0.60 ml) obtained in the first step, the conductive agent (Super P, 0.06 g) and 2 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, dried at 60°C for 12 hours, and pressed into a sheet to obtain a silicon-based negative electrode sheet.
[0109] Step 3: Prepare lithium-ion batteries
[0110] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0111] Step 4: Performance Testing
[0112] The button cell assembled in the third step was subjected to constant current charge and discharge test, where the voltage window was 0.005-1.5V and the current rate was 0.3C. The test results are as follows: Figure 6 shown.
[0113] Depend on Figure 6It can be seen that when polyvinyl alcohol-konjac glucomannan-polypyrrole-citric acid is used as a binder and silicon / carbon composite material is used as an active material, the battery has a high performance of 4 mAh cm -2 The high surface capacity can be stably cycled for 100 cycles, and the capacity retention rate is greater than 90%, indicating that the composite binder can effectively inhibit the volume expansion of the silicon / carbon composite material.
[0114] Embodiment 7
[0115] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0116] The first step is to prepare a composite binder aqueous solution
[0117] Dissolve polyacrylic acid (1.6 g, aqueous polymer binder), polyvinyl alcohol (1.4 g, aqueous polymer binder), konjac glucomannan (0.4 g, aqueous polymer binder) and citric acid (0.4 g, small molecule physical cross-linking agent containing carboxyl groups) in 40 ml of water, place in an ice bath at 0-5°C, add pyrrole (0.4 g) to the mixed solution, stir evenly, add 4 ml of ammonium persulfate aqueous solution (mass fraction 10%, initiator), stir at 400 r / min for 60 min, and obtain a composite binder aqueous solution.
[0118] Step 2: Prepare silicon-based negative electrode
[0119] Mix the silicon dioxide composite material (0.80 g), the composite binder aqueous solution (1.0 ml) obtained in the first step, the conductive agent (Super P, 0.10 g) and 2 ml of water, and stir for 24 hours to obtain a slurry; coat the slurry on a copper foil, vacuum dry at 150°C for 2 hours, dry at 80°C for 6 hours, and press into sheets to obtain a silicon-based negative electrode sheet.
[0120] Step 3: Prepare lithium-ion batteries
[0121] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0122] Step 4: Performance Testing
[0123] The button cell assembled in the third step is subjected to constant current charge and discharge test, where the voltage window is 0.01~1.5V and the current rate is 0.3C. The test results are as follows: Figure 7 shown.
[0124] Depend on Figure 7It can be seen that when polyacrylic acid-polyvinyl alcohol-konjac glucomannan-polypyrrole-citric acid is used as a binder and oxidized sub-material is used as an active material, the battery has a capacity of 3 mAh cm -2 The high surface capacity can be stably cycled for 100 cycles, and the capacity retention rate is greater than 90%, indicating that the composite binder can effectively inhibit the volume expansion of silicon oxide.
[0125] Embodiment 8
[0126] This embodiment prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, including the following steps:
[0127] The first step is to prepare a composite binder aqueous solution
[0128] Dissolve polyacrylic acid (2.7 g, water-based polymer binder) and citric acid (0.9 g, small molecule physical cross-linker containing carboxyl groups) in 35.2 ml of water, place in an ice bath at 0-5°C, add pyrrole (0.4 g) to the mixed solution, stir evenly, add 0.8 ml of ammonium persulfate aqueous solution (mass fraction 10%, initiator), stir at 500 r / min for 15 min, and obtain a composite binder aqueous solution.
[0129] Step 2: Prepare silicon-based negative electrode
[0130] Silicon micron particles (0.480 g), the composite binder aqueous solution (1.2 ml) obtained in the first step and 0.5 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, dried at 100° C. for 12 hours, and pressed into sheets to obtain a silicon-based negative electrode sheet.
[0131] Step 3: Prepare lithium-ion batteries
[0132] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0133] Step 4: Performance Testing
[0134] The button cell assembled in the third step was subjected to constant current charge and discharge tests, where the current density was 2A / g and the voltage window was 0.01-1V. The test results are as follows Figure 8 shown.
[0135] Depend on Figure 8 It can be seen that the battery with polypyrrole-polyacrylic acid-citric acid as the binder and silicon microparticles as the active material shows excellent cycle performance without adding a conductive agent, and the gram capacity is maintained at 1800mAh g -1As shown above, the capacity retention rate after 100 cycles is greater than 90%, which indicates that the composite binder can effectively improve the conductivity of the micron silicon negative electrode.
[0136] Comparative Example 3
[0137] The comparative example prepares a composite binder aqueous solution, a silicon-based negative electrode plate and a lithium-ion battery, comprising the following steps:
[0138] The first step is to prepare a composite binder aqueous solution
[0139] Dissolve polyacrylic acid (2.7g, water-based polymer binder) and citric acid (0.9g, small molecule physical crosslinker) in 35.2ml water, place in an ice bath at 0-5°C, add pyrrole (0.4g) to the mixed solution, stir evenly, add 0.8ml of ammonium persulfate aqueous solution (mass fraction 10%, initiator), stir at 500r / min for 15min, and obtain a composite binder aqueous solution (in which polypyrrole accounts for 10% of the composite binder). Use the same process to control the pyrrole content and prepare composite binder aqueous solutions with polypyrrole accounting for 5% and 30%.
[0140] Step 2: Prepare silicon-based negative electrode
[0141] Silicon micron particles (0.480 g), 1.2 ml of the composite binder aqueous solution with three polypyrrole contents obtained in the first step, and 0.5 ml of water were mixed and stirred for 24 hours to obtain a slurry; the slurry was coated on a copper foil, dried at 100°C for 12 hours, and pressed into a sheet to obtain a silicon-based negative electrode sheet.
[0142] Step 3: Prepare lithium-ion batteries
[0143] The silicon-based negative electrode sheet from the second step was cut and transferred to the glove box, and assembled into a 2032 button cell with a lithium sheet as the counter electrode. The electrolyte was an EC / EMC (volume ratio 3:7) solution with 1.2M LiPF6 as the electrolyte, and 10% of the FEC additive was added.
[0144] Step 4: Performance Testing
[0145] The button cell assembled in the third step was subjected to constant current charge and discharge tests, where the current density was 2A / g and the voltage window was 0.01-1V. The test results are as follows Figure 8 shown.
[0146] Depend on Fig. 9 It can be seen that when the polypyrrole content is 10%, the gram capacity of the micron silicon anode is the highest, reaching 2900mAh g -1 The cycling stability is also better. The cycling stability is similar when the polypyrrole content is 5% and 30%, but the gram capacity is slightly better when the polypyrrole content is 5%.
[0147] In summary: the preparation method of the composite binder aqueous solution provided by the present invention increases a large number of hydrogen bonding sites by introducing a small molecule physical cross-linking agent containing a carboxyl group into the aqueous polymer binder, thereby significantly enhancing the mechanical properties of the binder itself. The excellent mechanical properties of the binder further improve the processability of the electrode. At the same time, the binder can be polymerized in situ to generate polypyrrole, and through the strong interaction between the binder and the silicon particles, the polypyrrole can be tightly coated on the surface of the silicon particles to form a stable conductive network, which significantly improves the charge transfer capacity of the electrode.
[0148] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite binder aqueous solution, characterized in that: The method comprises the following steps: The aqueous polymer binder and the small molecule physical cross-linking agent are dissolved in water, pyrrole is added to the mixed solution, stirred, and then an initiator is added, and the stirring is continued to obtain a composite binder aqueous solution.
2. The preparation method according to claim 1, characterized in that The mass ratio of the aqueous polymer binder to the small molecule physical cross-linking agent is 1:1 to 3:
1.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the pyrrole to the mixed solution is 1:9 to 3:
7.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the pyrrole to the initiator is 3:1 to 5:
1.
5. The preparation method according to claim 2, characterized in that: The aqueous polymer binder is selected from one or more of polyacrylic acid, polyvinyl alcohol, carboxymethyl cellulose, sodium alginate, guar gum or konjac glucomannan; The small molecule physical crosslinking agent contains a carboxyl group, and the small molecule physical crosslinking agent containing a carboxyl group is selected from one of citric acid, oxalic acid or succinic acid.
6. A composite binder aqueous solution prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The mass fraction of the composite binder aqueous solution is 10-40%.
7. Use of the composite binder aqueous solution as claimed in claim 6 in silicon-based negative electrode plates.
8. A silicon-based negative electrode plate, characterized in that: It comprises the composite binder aqueous solution as claimed in claim 6 or 7, a silicon-based material and a conductive agent; The mass ratio of the composite binder aqueous solution, the silicon-based material and the conductive agent is 1-2:6-8:0-2.
9. A method for preparing the silicon-based negative electrode sheet as claimed in claim 8, characterized in that: The method comprises: stirring a composite binder aqueous solution, a silicon-based material and a conductive agent in water for 6 to 72 hours, coating the mixture on a current collector, drying at 40 to 150° C., and pressing to obtain a silicon-based negative electrode sheet.
10. Application of the silicon-based negative electrode plate as claimed in claim 8 in the field of lithium-ion batteries.
Citation Information
Patent Citations
Composite adhesive, preparation method thereof, lithium battery
CN105047935A
Preparation method of tannic acid cross-linked polypyrrole conductive polymer hydrogel and application thereof
CN113831556A
Sodium ion battery negative electrode, negative electrode slurry and negative electrode slurry preparation method
CN117096268A
Silicon-based negative electrode aqueous binder as well as preparation method and application thereof
CN117894990A
METHOD FOR PRODUCING METAL NANOPARTICLES PROTECTED FROM OXIDATION
RU2010145210A
Cited By
Conductive binder as well as preparation method and application thereof
CN120082324A
Aqueous binder, preparation method and application thereof, and sodium ion battery
CN120442193A
Silicon negative pole piece, sodium ion solid-state battery and preparation method of sodium ion solid-state battery
CN120674496A
Force-sensitive self-enhancing binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of force-sensitive self-enhancing binder
CN122011975A